(untitled) (Global Journal of Medical Research, 2022)
The scientific work presents the results of a neurophysiological examination of 63 patients with cerebellar symptoms in Chiari malformation of type I according to MRI data All patients underwent a multimodal protocol including BAEP SSEP and ENMG examination Neurophysiological criteria of the cerebellar syndrome in type 1 Chiari malformation have been identified which in a comparative analysis are the most informative in decision making regarding conservative or surgical treatment